Bacillus coagulans (BSCB-2) PROBIOTICS EFFECTS ON PHYSICAL PARAMETERS OF COLITIS INDUCED WISTAR RATS - GNANAM, T. SHALINI; KOLANCHINATHAN, P.; KUMARI, P. RATHNA; BALASUNDARAM, A. (UTTAR PRADESH JOURNAL OF ZOOLOGY, 2020)
Ulcerative colitis is a bowel inflammatory disorder which develops due to various reasons like heredity, food habitsand physiological stress in intestinal lumen. In this study, Bacillus coagulans probiotics was orally administered to dextran sulfate sodium (DSS) colitis induced rats. Physical parameters such as body weight, feed intake, water intake and hepatorenal somatic indices were studied. Group I: control (n=6) rats without any drug was maintained. Group II: administrated with DSS (5%) and Group III: B. coagulans probiotics were orally administrated. In group II, increased body weight was due to the hepatomegaly and renomegaly conditions and increased food and water intake to overcome the stress developed by DSS. In group III, the megalic conditions were revoked when compared to group II. Our study concluded that B. coagulans probiotics reduces inflammation and infiltrations in liver and kidney tissues of male albino Wistar rats.